Mechanisms for Managing the Circular Economy in Subsoil Use - MOCHALOVA, Lyudmila; SOKOLOVA, Olga; EREMEEVA, Olga (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
The article is devoted to the consideration of the mechanisms for managing the circular economy in the field of subsoil use. Mechanisms aimed at environmentally oriented management of business processes are considered by the authors as auxiliary, which support the main technical and technological mechanisms, implying the use of energy and resource-saving technology, the best available technologies, etc. The study of foreign and domestic experience in applying the concept of a circular economy, carried out by the authors, made it possible to identify such organizational and managerial mechanisms as intra-firm and inter-firm circular business models, hierarchical schemes for managing the cyclicity of production and consumption, and logistic methods for managing subsurface waste. Circular industrial clusters were considered as inter-firm circular business models that allow, on the basis of the merger of enterprises of the mineral resource complex, to achieve the integrated development of mineral deposits, the integrated use of extracted mineral raw materials, the complete extraction of minerals (reduction of losses), and the disposal of industrial waste.